(untitled) (Research, Society and Development, 2022)
Adolescence is an evolutionary stage full of physical, biological and psychological transformations. These changes can have significant impacts on the mental health of the young person, and, in certain situations, lead to suicide attempts or practices as a way of resolving difficulties and/or conflicts. This phenomenon is complex, has several causes and associated factors, and has been growing in recent years, especially in view of the COVID-19 pandemic. Thus, the present study aimed to carry out a theoretical study on strategies for preventing suicide in adolescence in face of the difficulties experienced in the current context. We also researched the factors that lead to depression, ideation, attempts, and suicide in adolescence, as well as possible prevention strategies. The method used was a narrative literature review. It was identified that the family group has the potential to generate positive and adequate relationships when it presents support and attachment among its members. Moreover, suicide prevention interventions that address issues related to mental health, as well as the importance and role of family relationships, training of professionals in the school context, multidisciplinary monitoring, recognition of signs of suicidal behavior, and referral to health professionals are essential. Moreover, early detection of these cases becomes essential to preserve the lives of adolescents. Another important factor to be highlighted is the cyberbullying that affects the daily lives of adolescents. We conclude that providing an opportunity for them to be listened to and monitored seems to be an effective strategy for preventing and coping with suicide.